A new chamigrane sesquiterpene from the basidiomycete Antrodiella albocinnamomea. Issue 2 (1st February 2023) - Luo, Cheng; Lou, Deng-Ji; Li, Yin-Fei; Yang, Lian; Shao, Lin-Jiao; Liu, Ji-Kai; Yang, Xiao-Yan
Abstract: One new chamigrane sesquiterpene, antroalbol A (1 ), was isolated from the cultures of the higher fungus Antrodiella albocinnamomea. Its structure was established by means of spectroscopic methods, and the absolute configuration of 1 was confirmed by single crystal x-ray diffraction analysis. The compound was evaluated for its cytotoxicity against five human cancer cell lines, but no significant cytotoxicity was found. Graphical Abstract: UF0001